Land cover and forest connectivity alter the interactions among host, pathogen and skin microbiome - Becker, C. G. [UNESP]; Longo, A. V.; Haddad, C. F. B. [UNESP]; Zamudio, K. R. (Royal Soc, 2017)
Deforestation has detrimental consequences on biodiversity, affecting species interactions at multiple scales. The associations among vertebrates, pathogens and their commensal/symbiotic microbial communities (i.e. microbiomes) have important downstream effects for biodiversity conservation, yet we know little about how deforestation contributes to changes in host microbial diversity and pathogen abundance. Here, we tested the effects of landcover, forest connectivity and infection by the chytrid fungus Batrachochytrium dendrobatidis (Bd) on amphibian skin bacterial diversity along deforestation gradients in Brazilian landscapes. If disturbance to natural habitat alters skin microbiomes as it does in vertebrate host communities, then we would expect higher host bacterial diversity in natural forest habitats. Bd infection loads are also often higher in these closed-canopy forests, which may in turn impact skin-associated bacterial communities. We found that forest corridors shaped composition of host skin microbiomes; high forest connectivity predicted greater similarity of skin bacterial communities among host populations. In addition, we found that host skin bacterial diversity and Bd loads increased towards natural vegetation. Because symbiotic bacteria can potentially buffer hosts from Bd infection, we also evaluated the bi-directional microbiome-Bd link but failed to find a significant effect of skin bacterial diversity reducing Bd infections. Although weak, we found support for Bd increasing bacterial diversity and/or for core bacteria dominance reducing Bd loads. Our research incorporates a critical element in the study of host microbiomes by linking environmental heterogeneity of landscapes to the host-pathogen-microbiome triangle.
Keywords: microbial diversity; deforestation; biodiversity; chytrid; spatial connectivity